1992
DOI: 10.1088/0963-0252/1/1/006
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of electron energy distribution in low-pressure RF discharges

Abstract: Electron energy distribution functions (EEnFs) have been measured in low-pressure capacitive R F discharges over a wide range of well defined (geometrically and electrically) discharge conditions. Measurements have been made in argon and helium ranging in gas pressure between 3mTorr and 3Torr and in discharge current density between 0.1 mAcm-Z and 10mAcm-Z. The measurements show changes in the EEDF due to the occurrence of physical phenomena such as stochastic electron heating and t h e effect of discharge tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
553
2
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 714 publications
(590 citation statements)
references
References 44 publications
32
553
2
3
Order By: Relevance
“…For our purpose, the absence of the ͱ −eU term in the EEPF eases the demonstration of differences in the shape of the distribution function. 18 Figure 1 shows the evolution of the EEPF with increasing power at 1.33 Pa. At 41 W in the E mode the EEPF is obviously a Maxwellian. At 47 W the low-energy part ͑be-low 5 eV͒ of the EEPF is slightly enhanced and has a steeper slope.…”
mentioning
confidence: 99%
“…For our purpose, the absence of the ͱ −eU term in the EEPF eases the demonstration of differences in the shape of the distribution function. 18 Figure 1 shows the evolution of the EEPF with increasing power at 1.33 Pa. At 41 W in the E mode the EEPF is obviously a Maxwellian. At 47 W the low-energy part ͑be-low 5 eV͒ of the EEPF is slightly enhanced and has a steeper slope.…”
mentioning
confidence: 99%
“…Two different dust density profiles were taken in our simulation: (a) one with a maximum in the center of the discharge gap, n d (x) = n max sin(π(x − l s )/(d − 2l s )), and (b) with two maxima near the electrode sheaths and a void in the gap center, which is often observed in experiments, n d (x) = n max sin 2 …”
Section: Resultsmentioning
confidence: 99%
“…However, it is known from experiments that in a capacitively coupled radio frequency (ccrf) discharge without dust the electron energy distribution function (EEDF) can be far from Maxwellian even in a bulk plasma. The EEDFs were measured in [2] in a ccrf discharge in helium and argon to illustrate the difference in the electron kinetics in non-Ramsauer and Ramsaur gases. It was shown that in helium the shape of the EEDF remains Maxwellian for all pressures.…”
Section: Introductionmentioning
confidence: 99%
“…The EEDFs are bi-Maxwellian with the two temperatures remaining approximately constant as a function of power. The bi-Maxwellian EEDF is now a well understood feature of low pressure CCP discharges [38].…”
Section: Measured Energy Distributions In the Ccp Reactormentioning
confidence: 99%